Ribosome preparation from turquoise killifish skeletal muscle for cryo-EM - Seongsin Lee; Yumi Kim (STAR Protocols, 2022)
Summary: Ribosomes are composed of a mix of ribosomal RNAs and proteins; this composition varies depending on time, condition, and organism. Here, we present an optimized protocol for preparation of intact ribosomes from the skeletal muscle of the turquoise killifish. We also detail the steps for ribosome quantification and cryo-EM grid preparation. This protocol can enable the identification of heterogeneous ribosome structures that vary by fish age or in response to specific conditions.